(untitled) (Revista Cocar, 2022)
Este texto apresenta o resultado de estágio pós-doutoral, desenvolvido na forma de curso de extensão, e buscou aprofundar estudos sobre a prática de contar história na perspectiva da formação continuada de sujeitos envolvidos na educação de crianças, jovens, adultos ou idosos em espaços educativos formais e informais. O principal objetivo do estudo-pesquisa e formação foi contribuir para as discussões levantadas sobre a tradicionalidade discursiva que ancora a contação de histórias. Para isso, foi realizada uma pesquisa colaborativa, na qual foram produzidos conhecimentos para o desenvolvimento profissional em dez encontros no formato de ciclos de estudos reflexivos e dialogados sobre a arte de contar histórias. Ao final dos encontros, cinquenta pessoas entre professores, psicólogos e agentes culturais apresentaram suas performances na contação de histórias. Palavras-chave: Formação docente; leitura; literatura; contação de histórias. Abstract This text presents the result of a post-doctoral internship, developed in the form of an extension course, and sought to deepen the studies of the practice of storytelling in the perspective of the continuing education of subjects involved in the education of children, young people, adults, or elderly people in formal and informal educational spaces. The main objective of the study-research-training was to contribute to the discussions raised about the discursive traditionality that anchors storytelling. For this, collaborative research was conducted, in which knowledge was developed for professional development in ten meetings in the format of reflective and dialogued study cycles on the art of storytelling. At the end of the meetings, fifty people, including teachers, psychologists, and cultural agents, presented their performances in storytelling with the subjects of education with whom they interact. Keywords: Teacher training; reading; literature; storytelling